Caça-Vento, Vida-sub & Bicho do Mato e a educação ambiental através das gerações: espaços não formais de educação - Gonçalves, Fernando Henrique Puertas [UNESP]; Chiquitelli Neto, Marcos [UNESP]; Dornfeld, Carolina Buso [UNESP]; Kanda, Claudia Zukeran [UNESP]; Queiroz, Murilo de Souza [UNESP]; Anjos, Luciano Alves dos [UNESP] (My University, 2014)
The preservation and conservation issues are addressed on a daily basis and are currently increasingly becoming part of everyday life for all of society, from this comes the projectCaça-Vento, Vida-sub & Bicho do Mato that focus on promoting civil society approach to the environmentalelements, raising awareness of preservation. More specifically this study are addressed visits covering a wide type of audience ranging from children undergoing special students and finally old age, these two often overlooked in the subject matter, Environmental Education. The study was grounded in phenomenology and provides important information about the environmental perception of the participants from various generations, and shows the effectiveness of the non-formal spaces education in the learning of all kinds of audiences.

A preservação e conservação ambiental são temas abordados diariamente atualmente e fazem cada vez mais parte do cotidiano de toda sociedade, partindo disso surge o Projeto Caça-Vento, Vida-sub & Bicho do Mato que têm como foco promover a aproximação da sociedade civil aos elementos ambientais, despertando a consciência da preservação. Mais especificamente nesse estudo são abordadas visitas que abrangem um vasto tipo de público que vão de crianças, passando por alunos especiais e por fim a terceira idade, esses dois geralmente negligenciados no assunto em questão, a Educação Ambiental. O estudo foi pautado na fenomenologia e traz informações importantes a cerca da percepção ambiental dos participantes de várias gerações, além de mostra a eficácia dos espaços não formais de educação no aprendizado dos mais variados tipos de públicos.
Keywords: Non-formal space education; Phenomenology; Environmental education; Espaço não formal de educação; Fenomenologia; Educação ambiental